Switchable and efficient conversion of 2-amido-aryl oxazolines to quinazolin-4(3H)-ones and N-(2-chloroethyl)benzamides. Issue 3 (11th December 2020) - Chen, Weiqiang; Liu, Mei; Li, Hui-Jing; Wu, Yan-Chao
Abstract : Switchable chemoselective conversion of 2-amido-aryl oxazolines to quinazolin-4(3 H )-ones or N -(2-chloroethyl)benzamides is achieved. Abstract : Switchable chemoselective conversion of 2-amido-aryl oxazolines to quinazolin-4(3 H )-ones or N -(2-chloroethyl)benzamides is achieved. The former reaction is proposed to involve a PIFA-mediated 6π electrocyclization followed by an in situ nucleophilic substitution, while the latter reaction uses aluminum chloride as a halogenated source through a ring-opening reaction. The reactions proceed smoothly under mild conditions and have excellent functional group compatibility.